Increased transcription and high translation efficiency lead to accumulation of androgen receptor splice variant after androgen deprivation therapy. (28th April 2021) - Ma, Tianfang; Bai, Shanshan; Qi, Yanfeng; Zhan, Yang; Ungerleider, Nathan; Zhang, Derek Y.; Neklesa, Taavi; Corey, Eva; Dehm, Scott M.; Zhang, Kun; Flemington, Erik K.; Dong, Yan
Abstract: Upregulation of androgen receptor splice variants (AR-Vs), especially AR-V7, is associated with castration resistance of prostate cancer. At the RNA level, AR-V7 upregulation is generally coupled with increased full-length AR (AR-FL); consequently, AR-V7 and AR-Vs collectively constitute a minority of the AR population. However, Western blotting showed that the relative abundance of AR-V proteins is much higher in many castration-resistant prostate cancers (CRPCs). To address the mechanism underlying this discrepancy, we analyzed RNA-seq data from ~350 CRPC samples and found a positive correlation between all canonical and alternative AR splicing. This indicates that increased alternative splicing is not at the expense of canonical splicing. Instead, androgen deprivation releases AR-FL from repressing the transcription of the AR gene to induce coordinated increase of AR-FL and AR-V mRNAs. At the protein level, however, androgen deprivation induces AR-FL, but not AR-V, degradation. Moreover, AR-V7 is translated much faster than AR-FL. Thus, androgen-deprivation-induced AR-gene transcription and AR-FL protein decay, together with efficient AR-V7 translation, explain the discrepancy between the relative AR-V mRNA and protein abundances in many CRPCs, highlighting the inevitability of AR-V induction after endocrine therapy. Highlights: Increase of AR-Vs in castration resistant prostate cancer is inevitable. Mechanism of increased expression of androgen receptor splice variants in CRPC. Mechanism of resistance to androgen deprivation therapy or AR-targeted therapy. AR-V7 is translated much faster than AR-FL. Androgen deprivation induces coordinated increase of AR-FL and AR-V mRNAs.